2013
DOI: 10.3390/insects4030392
|View full text |Cite
|
Sign up to set email alerts
|

A Third Way for Entomophthoralean Fungi to Survive the Winter: Slow Disease Transmission between Individuals of the Hibernating Host

Abstract: In temperate regions, insect pathogenic fungi face the challenge of surviving through the winter. Winter is a time when hosts are immobile, low in number or are present in a stage which is not susceptible to infection. Fungi from Entomophthoromycota have so far been known to survive the winter in two ways: either as (1) thick-walled resting spores released into environment from dead hosts, or as (2) structures inside the dead host (e.g., hyphal bodies). Here we report, from the Danish environment, a third way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…On the other hand, entomopathogenic fungi, which can cause high mortality of overwintering insect herbivores (Kienzle et al 2008;Kova et al 2021), have been considered as important lethal factors of insects and thus may have significant effects on insect herbivory (Vega et al 2009). Their growth and infection efficiency can be influenced by weather conditions (temperature and humidity) (Kienzle et al 2008;Eilenberg et al 2013), soil moisture (Fuxa and Richter 2004), and nutrition in the habitat (Pereira et al 1993;Jackson et al 2009). Our results showed that soil available N and K contents and soil moisture, as well as insect herbivory in the loam area, were significantly higher than that in the gravel soil area (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, entomopathogenic fungi, which can cause high mortality of overwintering insect herbivores (Kienzle et al 2008;Kova et al 2021), have been considered as important lethal factors of insects and thus may have significant effects on insect herbivory (Vega et al 2009). Their growth and infection efficiency can be influenced by weather conditions (temperature and humidity) (Kienzle et al 2008;Eilenberg et al 2013), soil moisture (Fuxa and Richter 2004), and nutrition in the habitat (Pereira et al 1993;Jackson et al 2009). Our results showed that soil available N and K contents and soil moisture, as well as insect herbivory in the loam area, were significantly higher than that in the gravel soil area (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…However, some, such as Beauveria bassiana , are able to grow at temperatures as low as 5 °C, albeit at a slow rate [ 65 ]. Eilenberg, et al [ 66 ] found that the entomophthoralean fungus Entomophthora schizophorae survives the winter in its host, the adult dipteran Pollenia sp., through slow disease development and transmission among hosts hibernating in clusters in unheated attics. Overwintering near entrances and in the twilight zone of caves and mines, where temperatures are relatively low, can reduce metabolism and hence extend food reserves in harvestmen and other arthropods [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 ). However, E. muscae infections have been observed even in winter months in buildings where hosts shelter from the elements (Kramer and Steinkraus 1981 ; Eilenberg et al 2013 ). Given what is known of the life-cycle of Entomophthora species (reviewed below), the broad global distribution of potential hosts for the fungus, and the fact that these fungi are woefully understudied, it seems reasonable to hypothesize that Entomophthora can be found throughout their host’s range, as opposed to only existing in subsets of these ranges.…”
Section: Who They Are Where To Find Them and Who They Killmentioning
confidence: 99%